(untitled) (Edinburgh, 2002)
The book provides an up-to-date overview of this controversial disease, focusing in particular on diagnosis, management and treatment, but also covering epidemiology and new pathophysiologic advances. Tailored to the needs of today's practicing clinician, the book clearly explains the role of diet in treatment of IBS, the use of antidepressants, bulking agents and antispasmodics, as well as including a thorough review of serotinergic drugs and emerging treatments and pharmacotherapies. The management of the disease from the primary care perspective, and the relationship between the doctor and the patient in the treatment of the disease, are also comprehensively covered
Keywords: Irritable colon,Colonic Diseases, Functional,Colonic Diseases, Functional; Treatment.,Diagnosis.,Therapy